REFLECTIONS ON HISTORIANS, HISTORIOGRAPHY, AND THE CONFESSIONAL DIVIDE. - Robert, Dana L. (Fides et historia, 2012)
The author reflects on denominational, Christian and confessional history in the U.S., including the confessional divide among Catholic, Protestant and evangelical histories, as well as mission histories. The author refers to his book ''Christian Mission: How Christianity Became a World Religion'' as an example of how both Catholic and evangelical history are intrinsic to the narrative of mission history in the country. The author emphasizes that the increase in global Pentecostalism and the surge of new denominations in Asia, Africa and Latin America indicates a revival within communal theological history.